2013
DOI: 10.1177/0333102413476370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental activation of the sphenopalatine ganglion provokes cluster-like attacks in humans

Abstract: LF SPG stimulation may induce cluster-like attacks with autonomic features, which can subsequently be treated by HF SPG stimulation. Efferent parasympathetic outflow from the SPG may initiate autonomic symptoms and activate trigeminovascular sensory afferents, which may initiate the onset of pain associated with CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…Even though the physiopathology of CH is still unknown, the hypothalamus is thought to be the generator of this disease because of its circadian and circannual periodicity and the activation of the posterior hypothalamus found in neuroimaging studies that were undertaken during the attacks. Furthermore, activation of the parasympathetic outflow from the superior salivary nucleus via the SPG is supposed, explaining the autonomic manifestations of CH and the likely role of the SPG at least in this aspect of the disease . Indeed, it was shown that low frequency (5 Hz) SPG stimulation could induce cluster‐like attacks with autonomic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the physiopathology of CH is still unknown, the hypothalamus is thought to be the generator of this disease because of its circadian and circannual periodicity and the activation of the posterior hypothalamus found in neuroimaging studies that were undertaken during the attacks. Furthermore, activation of the parasympathetic outflow from the superior salivary nucleus via the SPG is supposed, explaining the autonomic manifestations of CH and the likely role of the SPG at least in this aspect of the disease . Indeed, it was shown that low frequency (5 Hz) SPG stimulation could induce cluster‐like attacks with autonomic features.…”
Section: Discussionmentioning
confidence: 99%
“…According to the explanation of the authors, this induction may be due to the release of neurotransmitters from parasympathetic efferents, which activate or at least modulate trigeminal nociceptors. On the other hand, high frequency (80 to 120 Hz) SPG stimulation may activate sensory fibers from the maxillary nerve, which converge in the trigeminal nucleus caudalis with afferents from the ophthalmic branch, leading to antinociceptive modulatory changes . It is important since the pain of CH is thought to be due to activation of the ophthalmic nerve .…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led to several speculations on the possible mechanisms of action of SPG stimulation in aborting CH attacks. The authors suggested that the therapeutic effect of high frequency stimulation might be caused by physiological block of parasympathetic activity as a result of depletion of stored neurotransmitters [13].…”
Section: Sphenopalatine Ganglion Stimulationmentioning
confidence: 99%
“…The SPG is located in the pterygopalatine fossa and contains parasympathetic and sympathetic fibers directly and indirectly connecting somatic and visceral nerve structures of the face to the trigeminovascular system, the superior salivatory nucleus in the brainstem and the hypothalamus. In cluster headache patients, low-frequency stimulation of the SPG can induce cluster-like attacks which can be aborted by high-frequency stimulation [26]. One proof of concept study found that in 6 patients, 11 out of 18 spontaneous or induced CH attacks were aborted by stimulating the SPG [27].…”
Section: Sphenopalatine Ganglion (Spg) Stimulationmentioning
confidence: 99%